Single-sided deafness and unilateral auditory deprivation in children: current challenge of improving sound localization ability. Issue 1 (January 2020) - Liu, Jinfeng; Zhou, Mo; He, Xiaolin; Wang, Ningyu
Interaural time difference and interaural level difference signals are insufficient in patients with single-sided deafness (SSD). This insufficiency leads to an absence of sound localization abilities and a decrease in speech intelligibility in noisy environments. SSD occurring in children further affects their language learning and cognitive abilities and their academic performance because they lack spatial abilities and binaural hearing. The early stages of central auditory system development are critical for auditory function development and morphological refinement. SSD occurring in the critical period can cause significant lateralization in the bilateral auditory pathway. This may increase the risk that affected individuals cannot re-establish binaural benefits after rehabilitation of hearing loss in the post-sensitive period. For otorhinolaryngologists, there is the concern that children with congenital SSD cannot benefit from cochlear implantation. Only a few studies have investigated auditory rehabilitation in children with congenital SSD with cochlear implantation and their results were inconsistent. The present review aims to clarify the main problems and challenges of clinical rehabilitation of congenital SSD, particularly focusing on the effect of CI on sound localization ability in children with congenital SSD.